Role of Justice Collaborators in Uncovering Terrorist Networks: Effectiveness Analysis in Indonesia’s Criminal Justice System: Peran Saksi Pelaku yang Bekerjasama (Justice Collaborator) dalam Mengungkap Jaringan Terorisme: Analisis Efektivitas dalam Sistem Peradilan Pidana Indonesia - Muhammad Faiq Zuhrul Anam; Shofriya Qonitatin Abidah (Indonesian Journal of Counter Terrorism and National Security, 2025)
Terrorism is a type of organized crime that falls into the category of extraordinary crime. Overcoming this also requires the use of extraordinary measures. Justice collaborator (JC) is a scheme that can optimize the process of handling criminal acts of terrorism, which not only includes repressive efforts (penal path) but prevents similar crimes from occurring early by revealing a wider terrorist network. This study analyzes the role of justice collaborators (JC) in revealing terrorist networks and the effectiveness of their application in the criminal justice system. This study is a type of juridical-normative research using a statute approach. The role of justice collaborators (JC) in revealing terrorist networks has been regulated in several rules that are separate from regulations on overcoming criminal acts of terrorism. The non-single legal basis gives rise to different interpretations, thus having implications for the ineffectiveness of the role of justice collaborators (JC) in revealing terrorist networks. This can be seen from the absence of a unified coordination of law enforcement officers to ensure the fulfillment of the rights of protection and appreciation for justice collaborators (JC). The implementation in the criminal justice system raises several obstacles, including the mechanism, multi-agency coordination, qualifications, and credibility of the perpetrators who are made justice collaborators (JC). This study concludes that there needs to be an update to regulating justice collaborators (JC) into a single law binding on all criminal justice institutions. There are two update mechanisms: creating a single law or including it in the Criminal Code Bill. Further research is expected to deepen the understanding of empirical data and the use of normative data.